The effect of long-term high-fat diet in ovariectomized Wistar rat (Rattus norvegicus)study on lipid profile, endothelial nitric oxide synthase(eNOS) dan endhotelin-1 (ET-1) serum - Tantri Analisawati Sudarsono; Denny Agustiningsih; S Sunarti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Accumulation of cholesterol in the blood will cause stiffness in arteries and trigger the formation of atherosclerotic lesions. Estrogen has a role as an antioxidant that can prevent the low density lipoprotein(LDL) oxidation. In menopause with high-fat diet, the decrease of estrogen levels will trigger cholesterol accumulation in the blood lead to endothelial dysfunction mediated by endotelin-1 (ET-1) and nitric oxide synthase (eNOS). This study aimed to investigate the effect of long-term high-fat diet on the lipid profile, serum eNOS and ET-1levels on ovariectomized rat. It was experimental using 28 female Wistar rat divided into 4 groups. Group 1 was ovariectomized mice and given a standard diet (OVX-SD), Group 2 was ovariectomized mice and given a high-fat diet (OVX-HFD), Group 3 was not ovariectomized mice and given a standard diet(SHAM-SD) group, and Group 4 was not ovariectomized mice and given a high-fat diet (SHAM-HFD).Lipid profile of blood samples was measured pre- and post-treatment, whereas serum eNOS and ET-1 levels were measured post-treatment using ELISA method. No significantly difference of lipid profileon OVX-HFD group compared to that OVX-SD was observed. The serum eNOSlevel on OVX-HFD(702.11±68.73 pg/mL) was significantly lower than that OVX-SD (857.18±118.08 pg/mL) (p<0.05). However, there was no significantly different of serum ET-1 levelbetween OVX-HFD group (299.14±146.61 pg/mL) compared to that OVX-SD (194.25±102.96 pg/mL) (p>0.05). In conclusion, the serum eNOS levelon ovariectomized rat with long-term high-fat diet is lower than that on ovariectomized rat with standard diet.